Managing international debt: State of the art - Jesko Hentschel (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1988)
The cooperation between international organizations, private banks, and national governments as put forward in the Baker Plan has prevented major disruptions of the international financial system resulting from the debt crisis. Rescheduling agreements have been reached in large numbers. Financial innovations have provided flexibility to the banking system in dealing with their large exposure. But the disappointing response to the Mexican debt-swap initiative has also shown that financial innovations cannot be relied on solely to reduce the debt burden to levels that reestablish the credibility of major debtors. Structural adjustment efforts under the supervision of the IMF do not show the desired results either - more often proposals are put forward which demand a reexamination of some ingredients of the old debt management strategy. The conventional approach and new proposals are evaluated below.
Keywords: 330